Antifungal potential of commercial silver nanoparticles against rice blast pathogen Magnaporthe oryzae (Annals of Bangladesh Agriculture, 2024)
The rice blast caused by Magnaporthe oryzae is one of the major and recurrent threats to sustainable rice production in Bangladesh. To mitigate this problem, the present study was undertaken with the aim to investigate the inhibitory effects of commercially available silver nanoparticles (Ag-NPs) on the growth and development of Magnaporthe oryzae, and control of rice blast disease. In vitro experiments demonstrated that Ag-NPs significantly suppressed the radial growth of fungal mycelium, with the highest inhibition (83.54%) at a concentration of 250 ppm, while Trooper 75 WP at 400 ppm completely inhibited the fungal mycelial growth. The production of conidia and colony formation were also reduced significantly by Ag-NPs treatment. Furthermore, Ag-NPs exhibited a substantial inhibitory effect on the germination of M. oryzae conidia, with complete inhibition observed at concentrations between 200 and 250 ppm. Comparative analyses revealed that the fungicidal effect of Ag-NPs was superior to silver nitrate (AgNO3), suggesting the augmented activity of the nano properties. The sensitivity of M. oryzae to Ag-NPs was determined by calculating EC50 and EC95 values, which indicated a mean EC50 value of 131.5 ppm and a mean EC95 value of 276 ppm. Additionally, in vivo experiments showed that preventive and curative treatments with Ag-NPs significantly reduced disease incidence and severity in rice plants infected with M. oryzae, with efficacy comparable to that of the fungicide Trooper 75 WP. At higher concentrations of Ag-NPs, preventive treatment was found to be more effective than curative treatment in disease control. These findings highlighted the potential of Ag-NPs as an effective alternative for the management of rice blast.Ann. Bangladesh Agric. (2023) 27 (1): 17-30